Understanding the intertwined dynamics between digitalization, homelessness and social marginalization – An integrative literature review - Huhtasalo, Jenni; Vähätalo, Mervi; Niemi, Veera; Hietala, Sara; Rasinkangas, Jarkko (Finnish Social and Health Informatics Association, 2026)
The digital age offers significant benefits such as enhanced connectivity and improved access to information, but it also presents challenges for vulnerable populations, such as people experiencing homelessness and social marginalization. This integrative literature review explores the intertwined dynamics between digitalization, homelessness, and social marginalization, with the aim to understand how digitalization of society can, both facilitate social inclusion and well-being, and simultaneously reinforce exclusion among individuals facing housing insecurity and societal marginalization. The review is based on 28 peer- reviewed articles published in English between 2014 and 2024, retrieved from four databases (Google Scholar, SAMK-Finna, PubMed, Scopus). The findings reveal that people experiencing homelessness encounter substantial digital barriers, including (1) physical and technical barriers, (2) barriers in digital service system, (3) security, trust and privacy barriers and (4) socio-economic gaps and social marginalization. Despite these challenges, digital tools also provide opportunities for (5) better access to health care and services, (6) enhance social connections and empowerment and (7) digital inclusion and access to information. While some of these main categories may appear self-evident, our nuanced synthesis of the existing research underscores their complex interconnectedness and draws attention to less-explored dimensions. These include challenges related to digital identification, the significance of service content design and representation, issues of trust and psychological barriers, as well as the potential for enhanced continuity and engagement in digital services, and various dimensions of empowerment. Despite these challenges, digital tools also provide opportunities for accessing critical services, enhancing personal agency, fostering social connectedness and supporting self-management and control over one´s own life.  Furthermore, digital services support managing and having control over their own lives.